Development of a Potential Penside Colorimetric LAMP Assay Using Neutral Red for Detection of African Swine Fever Virus - Wang, Yang; Dai, Junfei; Liu, Yongsheng; Yang, Jifei; Hou, Qian; Ou, Yunwen; Ding, Yaozhong; Ma, Bing; Chen, Haotai; Li, MiaoMiao; Sun, Yuefeng; Zheng, Haixue; et al. (Frontiers in Microbiology, 2021)
African swine fever (ASF) has caused huge economic losses to the swine industry worldwide. Since there is no commercial ASF vaccine available, an early diagnosis is extremely important to prevent and control the disease. In this study, ASF virus (ASFV) capsid protein-encoding gene (p72) was selected and used to design primers for establishing a one-step visual loop-mediated isothermal amplification (LAMP) assay with neutral red, a pH-sensitive dye, as the color shift indicator. Neutral red exhibited a sharp contrast of color change from faint orange (negative) to pink (positive) during LAMP for detection of ASFV. The designed primer set targeting highly conserved region of the p72 gene was highly specific to ASFV and showed no cross-reactivity with other swine viruses. The detection limit for the one-step visual LAMP developed was 10 copies /reaction based on the recombinant plasmid containing the p72 gene of ASFV. More importantly, the developed one-step visual LAMP showed high consistency with the results of the real-time polymerase chain reaction (qPCR) method recommended by World Organization for Animal Health (OIE). Furthermore, the results demonstrate that the colorimetric detection with this LAMP assay could be directly applied for the whole blood and serum samples without requiring genome extraction. Based on our results, the developed one-step visual LAMP assay is a promising penside diagnostic tool for development of early and cost-effective ASF monitoring program that would greatly contribute to the prevention and control of ASF.